Wavelet Coherence as a Research Tool for Stability of the Banking System (the Example of Ukraine) - Pogorelenko, N.; Lyashenko, V.; Mohammad, A. (Scientific Research Publishing, 2016)
The banking system presents an open, multifaceted and meaningful set of different institutional units within a single monetary market. The effectiveness of such a system also largely determines the set of continuous mobilities of financial flows, and the result should determine the stability of the banking system. Accordingly, the work reveals a set of indicators of banking system stability and expediency analysis of available values using wavelet analysis. Wavelet coherence is considered a tool for wavelet analysis. Based on the analysis we displayed the impacts on the stability of the banking system in Ukraine in 2005-2015 years.
Keywords: Banking; Wavelet Coherence